2018
DOI: 10.3892/ijo.2018.4299
|View full text |Cite
|
Sign up to set email alerts
|

Increased interleukin-17A levels promote rituximab resistance by suppressing p53 expression and predict an unfavorable prognosis in patients with diffuse large B cell lymphoma

Abstract: Rituximab resistance has become increasingly common in patients with diffuse large B cell lymphoma (DLBCL). However, the mechanisms involved remain unclear. In this study, we aimed to examine the effect of rituximab on interleukin (IL)-17A and to investigate the role of IL-17A in rituximab resistance and its prognostic value in patients with DLBCL. Our retrospective analysis revealed that rituximab increased IL-6 expression levels in patients with DLBCL, and the increased IL-6 levels in turn induced the differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 39 publications
3
25
1
Order By: Relevance
“…49 Higher levels of IL-17A promotes rituximab resistance and serves as useful prognostic marker predicting unfavorable survival in patients with diffuse large B-cell lymphoma. 50 Recently, Zhu et al demonstrated that andrographolide, an anti-inflammatory compound isolated from Andrographis paniculata , can decrease the levels of IL-17A among other proinflammatory factors and suggested its therapeutic potential against ulcerative colitis. 51…”
Section: Discussionmentioning
confidence: 99%
“…49 Higher levels of IL-17A promotes rituximab resistance and serves as useful prognostic marker predicting unfavorable survival in patients with diffuse large B-cell lymphoma. 50 Recently, Zhu et al demonstrated that andrographolide, an anti-inflammatory compound isolated from Andrographis paniculata , can decrease the levels of IL-17A among other proinflammatory factors and suggested its therapeutic potential against ulcerative colitis. 51…”
Section: Discussionmentioning
confidence: 99%
“… 16 Contradictory results in the clinics have correlated the increase of Th17 with either a good 50 or a bad prognosis. 51 Interestingly, in B-NHL, we found that circulating Th17 frequencies in relapsed patients are significantly higher than those in untreated patients or normal individuals. 52 …”
Section: Discussionmentioning
confidence: 65%
“…16 Contradictory results in the clinics have correlated the increase of Th17 with either a good 50 or a bad prognosis. 51 Interestingly, in B-NHL, we found that Figure 7. No-alpha mutein maintains the long-lasting protection conferred by the anti-CD20 mAb.…”
Section: Discussionmentioning
confidence: 87%
“…In classical B-cell lymphoma, circulating Th17 cells have a lower number in diagnosed patients versus healthy individuals. However, in B-cell lymphoma patients [47], it was proven that the Th17 cells sustain rituximab resistance [48], having a higher number in recurrent disease [47]. This may be caused by the fact that Th17 cells stimulate B-cell proliferation independent of B-cell normal or lymphomagenesis status.…”
Section: T Cell and B Cell Subpopulation Types And Their Interplay Inmentioning
confidence: 99%